Booklet design for english language teaching to tourism employees from “playa almendro” resort in tonsupa, esmeraldas, 2018. - Córdova Montaño, Edwin Daniel (2019)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés